Effects of Revalor-G®, R®algro, and Synovex-H® on the performance of stocker heifers grazing irrigated rye pasture - Kuhl, Gerry L.; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 151-day field study was conducted to compare three anabolic implants for promoting weight gain in stocker heifers grazing center pivot-irrigated pastures of winter rye. Three hundred previously nonimplanted heifers averaging 421 lb were allotted to one of four treatments: 1) no implant-control (NC), 2) Ralgro® (RAL), 3) Revalor-G® (REV-G) and 4) Synovex-H® (SYN-H). Heifers were weighed at monthly intervals to evaluate the growth response curve of each implant type over time relative to controls. Only during the first 32-day period after implantation did heifers implanted with REV-G gain significantly faster (P<.05) than NC. All implant groups responded similarly (P>.05) during the next three monthly weigh periods. During the last period (day 124- 151), SYN-H heifers gained faster (P<.05) than all other treatments. Over the entire 151-day study, daily gains (lb/day) averaged as follows: NC, 1.50; RAL, 1.58; REV-G, 1.64; and SYN-H, 1.79. All implant types except RAL significantly improved gain (P<.05) compared to NC. Although no significant difference (P>.24) occurred between RAL and REV-G, SYN-H-implanted heifers. gained faster (P<.05) than the other implant groups over the 151-day grazing season.
Keywords: Beef; Growth implant; Revalor-G; Ralgro; Synovex-H; Heifers; Rye pasture